1997
DOI: 10.1016/s0092-8674(00)80186-5
|View full text |Cite
|
Sign up to set email alerts
|

Altered Ca2+ Responses in Muscles with Combined Mitochondrial and Cytosolic Creatine Kinase Deficiencies

Abstract: We have blocked creatine kinase (CK)-mediated phosphocreatine (PCr) -->/<-- ATP transphosphorylation in skeletal muscle by combining targeted mutations in the genes encoding mitochondrial and cytosolic CK in mice. Contrary to expectation, the PCr level was only marginally affected, but the compound was rendered metabolically inert. Mutant muscles in vivo showed significantly impaired tetanic force output, increased relaxation times, altered mitochondrial volume and location, and conspicuous tubular aggregates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
312
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(348 citation statements)
references
References 45 publications
35
312
0
1
Order By: Relevance
“…We think that NMR data give a better reflection of the actual metabolite levels than the chemical method, because minor energy metabolite changes can be induced by the freezing procedure. In another report [42] we have provided evidence that the PCr pool does not exchange with ATP and is metabolically completely inert, even under conditions of complete hypoxia. This leaves the question how and when Earlier, we had reported that resting-state glycogen content and the ability to consume this glycogen was about 60% increased in M-CK muscle compared to wild-type [28] mainly due to an increase in fast-type fibers.…”
Section: Metabolite Levelsmentioning
confidence: 87%
See 2 more Smart Citations
“…We think that NMR data give a better reflection of the actual metabolite levels than the chemical method, because minor energy metabolite changes can be induced by the freezing procedure. In another report [42] we have provided evidence that the PCr pool does not exchange with ATP and is metabolically completely inert, even under conditions of complete hypoxia. This leaves the question how and when Earlier, we had reported that resting-state glycogen content and the ability to consume this glycogen was about 60% increased in M-CK muscle compared to wild-type [28] mainly due to an increase in fast-type fibers.…”
Section: Metabolite Levelsmentioning
confidence: 87%
“…Details on the physiological consequences of CK ablation have been published [13,31,42]. All observations relate to the testing of muscle performance upon artificial electrical stimulation, ex vivo.…”
Section: Physiology and Cytoarchitectural Adaptationsmentioning
confidence: 99%
See 1 more Smart Citation
“…6(F)), a clear demonstration that the magnitude of exchange had decreased below MRS detection. In these mice PCr was found to be almost metabolically inactive (Steeghs et al 1997;In 't Zandt et al 1999a). This technique has also been applied to human skeletal muscle (for example, see Rees et al 1989).…”
Section: Muscle Bioenergetics As Observed By Dynamic 31 P Magnetic Rementioning
confidence: 97%
“…This is facilitated by keeping the local ATP/ ADP ratio high at subcellular sites near cellular ATPases via associated cytosolic MM-CK; this is especially important, for example, in the vicinity of the energetically highly demanding Ca 2+ -ATPase or calcium pump at the sarcoplasmic reticulum (SR), or in conjunction with the sarcolemma Na + /K + -ATPase, where fractions of cytosolic MM-CK are co-localized (Wallimann et al 2011). Supporting such an explanation is the most striking phenotype of the double-CK knockout mouse, which presents with significant difficulty with muscle relaxation (Steeghs et al 1997;Abraham et al 2002), or conversely, by keeping the ADP/ATP ratio high in the vicinity of the mitochondrial ADP/ATP-carrier (ANT) in a tight functional micro-compartment with mitochondrial mtCK (Wallimann et al 2011).…”
Section: Creatine Transporter (Crt) and Crt Deficiencymentioning
confidence: 99%